Creaphididae, A New and the Oldest Aphid Family From the Triassic of Middle Asia - Dmitri E. Shcherbakov; Piotr Wegierek (Psyche: A Journal of Entomology)
The only aphid specimen recorded in pre-Jurassic strata is the holotype forewing of Triassoaphis cubitus, which has not been referred to any family (Evans 1956. Heie 1987). Recently, another specimen has been discovered among numerous Triassic Homoptera collected in the rich locality. Dzhailou-Tcho (South Fergana, Middle Asia), and deposited in the Paleontological Institute (Moscow). According to paleobotanical data, the locality is of Ladinian-Carnian age, i.e., roughly synchronous or somewhat older than Carnian Ipswich Group (Dobruskina 1982) that harboured Triassoaphis. The newly found aphid is very primitive and peculiar enough to merit new family status.